Assessing the role of race in pathological upstaging of renal cell carcinoma: Results from the National Cancer Database. Issue 4 (22nd November 2020) - Suss, Nicholas R.; Bruha, Matthew J.; Monaghan, Thomas F.; Robins, Dennis; Flores, Viktor; Agudelo, Christina W.; Smith, Matthew; Hyacinthe, Llewellyn; McNeil, Brian K.; Weiss, Jeffrey; Winer, Andrew
Abstract: Purpose: Pathologic upstaging in renal cell carcinoma (RCC) is common and confers a significant risk of poor surgical and survival outcomes. Preoperative predictors of upstaging are of great clinical relevance but empirical evidence specific to racial minorities remains scarce. Methods: National Cancer Database (NCDB) analysis of T3a‐specific upstaging among White, African‐American, Hispanic and Asian Pacific Islander (API) patients with AJCC cT1N0M0 RCC who underwent partial or radical nephrectomy between 2010 and 2015. Independent preoperative predictors of tumour upstaging were identified using multivariate logistic regression analyses. Results: A total of 81 002 patients met the criteria for inclusion (5.6% T3a‐specific upstaging). Increased age, increased Charlson‐Deyo comorbidity index, clinical stages cT1b and unspecified cT1, and increased Fuhrman nuclear grade were identified as independent risk factors for upstaging. Independent protective factors for upstaging were younger age, female sex, African‐American race and papillary, chromophobe, and unspecified RCC histologic subtypes. Significant risk factors and protective factors within individual racial subgroups were highly consistent with those observed in the overall study sample. All independent factors identified on race‐specific subgroup analyses were significant in the same direction relative to the overall study sample. Variables found to be non‐significant in the overall study sample remained non‐significant across all racial subgroup analyses. Conclusion: The present study of nationally representative data found no clinically significant differences in upstaging risk across individual racial subgroups relative to the overall study sample. Preoperative factors that can be used to predict pT3a‐specific tumour upstaging in CT1N0M0 RCC likely persist across different racial groups.